The Representation of Society Criticism on Meme (Semiotic Analysis of Charles Sanders Pierce on Politician Billboard Memes) - Pratama Effendi, Ariel (Advances in Social Sciences Research Journal, 2022)
This research aims to discover the meaning of three previously selected memes that highlight the practice of placing billboards for Indonesian politicians outside of the 2024 presidential election campaign using semiotic analysis from Charles Sanders Pierce with a descriptive qualitative approach. The three memes that are the subject of this research are three memes that have a high virality value and are included in Twitter’s Trending Topics. The findings of this research show that the three memes have a negative attitude against the action of placing political billboards. These negative viewpoints are summed up in four key points that emerge from the three memes, namely (1) Criticism of installing billboards for politicians that are excessive in number and placement, (2) Criticism of the unimportance of installing billboards by politicians compared to other issues that are also being viral in the world. Twitter, (3) Criticism of the lack of empathy of politicians towards people who are experiencing economic difficulties in the midst of the second wave of the Covid-19 pandemic and (4) Criticism of politicians who only want to advertise themselves. In addition, the use of signs in the memes studied uses general signs that are close to the Indonesian people as well as things that are going viral close to the viral billboard phenomenon, such as The Beatles Album Cover, Tinder Dating App Logo, footballer Lionel Messi.